The Authority of Local Governments in Establishing Public Burial Land in the Spatial Planning of Urban Areas Purwokerto - Amardyasta Galih Pratama; Sri Wahyu Handayani; Sri Hartini; Siti Kunarti (Faculty of Law, Universitas Jenderal Soedirman, 2021)
The handover of the authority of the central government to the local government as a form of decentralization in the unitary state in the field of spatial planning, especially green open space in the form of burial land in the Banyumas Regency area, can be said to have not been effective in utilization and management like other forms of green open space. This is because it is not in accordance with the application of spatial planning as a form of green open space because there are discrepancies in its application to regional regulations that are not in line with higher regulations. This research uses a statutory and conceptual approach method with normative juridical research specifications. Using secondary data sources are then analyzed using deductive methods. Based on the results of the study, it can be concluded that there are deviations in legal norms in the content material for the management of burial land in Article 5 paragraph (3) of Banyumas Regency Regional Regulation Number 2 of 2014 concerning Burial Place Management which is contrary to Chapter II of the Provision of Green Open Space in Urban Areas in Green Open Spaces certain functions in Cemeteries listed in the Regulation of the Minister of Public Works Number 5 of 2008 concerning Guidelines for Provision and Utilization of Green Open Space in Urban Areas.Keywords: Decentralization, Green Open Space, Burial Land